‘Better she gets infected by other diseases but not pregnancy’. Narratives from adolescent girls and community males following pregnancy escalation during COVID-19 lockdown - Mason, Linda; Awiti, Enid; Young, Sophie; Otieno, Fredrick; Zulaika, Garazi; Phillips-Howard, Penelope; Mehta, Supriya D. (Frontiers in Reproductive Health, 2025)
IntroductionAdolescent sexual and reproductive health in low- and middle-income countries is critical to address following the COVID-19 pandemic. Growing evidence of its’ impact includes increased teenage pregnancies and higher rates of unsafe abortion. Our qualitative study sought to understand perspectives and behaviours around these escalations.MethodsUsing random sampling we conducted focus group discussions with adolescent girls and young women (AGYW) from western Kenya to understand perceptions and behaviours that drove high rates of pregnancy and abortion. Alongside, male opinions were sought using opportunistic sampling to recruit participants.ResultsSix FGDs with AGYW (n = 54) and five with community males (n = 53) were conducted with data analysed using thematic analysis. Results were grouped under 4 themes: (1) Fear, responsibility and blame; (2) Drivers of abortion; (3) Accessing an abortion; (4) Family planning including condom use. AGYW narratives revealed a dread of unintended pregnancy fearing parental and community reactions whilst men feared unfair blame from the community for impregnating AGYW despite admissions of sexual relationships with schoolgirls. Abortion attempts were common, girls described clandestine bids, including ingestion of dangerous or ineffective products, methods corroborated by the men. Many participants, male and female did nothing to mitigate pregnancy risks, disliking condoms and perceiving family planning as a threat to future fertility, or giving license to girls’ promiscuity.ConclusionAGYW remain at high pregnancy and unsafe abortion risk until community attitudes and knowledge are challenged. Our findings highlight the need for information and education to dispel myths and misinformation regarding family planning methods, and address inequities in gender norms. Safe, legal and affordable abortion is also paramount. Follow-up is required to assess long term physical and psychological consequences of the high number of unwanted pregnancies and abortions, particularly amongst those who had a failed abortion.